Cirugía menor en atención primaria: la satisfacción de los usuarios - López Santiago, A. (Aten Primaria, 2000)
OBJECTIVE: To find the satisfaction of patients undergoing minor surgery at health centres and describe the processes. DESING: Retrospective study of population seeking the service. SETTING: Health district. PATIENTS: 160 people who had minor surgery during a year. MEASUREMENTS AND MAIN RESULTS: Descriptive variables of everyone who had minor surgery were analysed: age, sex, type of intervention, pre-surgical diagnosis, anatomicalpathological diagnosis and informed consent. Over three weeks the patients were interviewed by phone with use of a satisfaction questionnaire. 160 interventions took place, 80% of which were then studied histologically, with an 83.16% concordance index. 65% of patients were interviewed. 15% had no telephone, 20% were not found. 95.56% considered they were well attended and 3.17% badly attended. 92.06% would choose the health centre again for procedures of a similar nature. 89.9% thought that the explanations they had received were sufficient. 4.4% thought that the room’s hygiene was poor. CONCLUSIONS: Minor surgery in primary care was favourably received by users. Activity at our centre had good anatomical-pathological concordance.